Social policy review. - Greener, Ian; Holden, Chris, 1965-; Kilkey, Majella (Book collections on Project MUSE., 2010)
'Social Policy Review 22' presents an up-to-date and diverse review of the best in social policy scholarship. It brings together specially commissioned reviews of key areas, research examining important debates in the field, and considers a range of issues including assessments of Labour's social policy after three terms in office, service-user involvement and the labour market impact of the economic crisis along with the winner of the SPA's best postgraduate paper award.